2003
DOI: 10.1038/sj.npp.1300201
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glucocorticoid Rhythm Attenuates the Ability of a Chronic SSRI to Elevate Forebrain 5-HT: Implications for the Treatment of Depression

Abstract: Both glucocorticoids and selective serotonin reuptake inhibitors (SSRIs) alter aspects of 5-HT function including somatodendritic 5-HT 1A autoreceptor sensitivity. Many depressed patients prescribed SSRIs have pre-existing flattened diurnal gluococorticoid rhythm. In these patients, interactions between flattened glucocorticoid rhythm and chronic SSRIs, which impact on the SSRI's ability to elevate forebrain 5-HT, may alter clinical efficacy. To address this issue rats underwent implantation of slow-release co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…1), but this response was less pronounced in the latter group, suggesting a functional desensitization of 5-HT 1A autoreceptor. These findings are consistent with initial studies showing that maternal separation or UCMS in rodents (Lanfumey et al, 1999;Gartside et al, 2003;Froger et al, 2004;Bambico et al, 2009) reduced 5-HT 1A autoreceptor sensitivity. When fluoxetine was given for 28 days, the hypothermic response to 8-OH-DPAT was also significantly attenuated in both vehicle-and corticosterone-pretreated mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…1), but this response was less pronounced in the latter group, suggesting a functional desensitization of 5-HT 1A autoreceptor. These findings are consistent with initial studies showing that maternal separation or UCMS in rodents (Lanfumey et al, 1999;Gartside et al, 2003;Froger et al, 2004;Bambico et al, 2009) reduced 5-HT 1A autoreceptor sensitivity. When fluoxetine was given for 28 days, the hypothermic response to 8-OH-DPAT was also significantly attenuated in both vehicle-and corticosterone-pretreated mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Recent evidence has suggested that 5-HT 1A receptor sensitivity in the dorsal raphe nucleus and the hippocampus may be altered by prolonged glucocorticoid administration (Fairchild, Leitch, & Ingram, 2003;Karten, Nair, van Essen, Sibug, & Joëls, 1999), and this may have consequences for 5-HT neurotransmission in key projection regions such as the frontal cortex (Gartside, Leitch, & Young, 2003;see Porter, Gallagher, Watson, & Young, 2004, for a review of the evidence for effects of glucocorticoids on 5-HT function in humans).…”
Section: Interactions Between the 5-ht System And The Hpa Axismentioning
confidence: 99%
“…Implantation of corticosteroid-releasing pellets in rodents to induce an HPA axis dysregulation has been shown to attenuate the ability of antidepressants to elevate forebrain 5-HT levels. 16 Interestingly, there is also increasing evidence that antiglucocorticoid treatments have the opposite effect by enhancing the forebrain 5-HT response to antidepressants. 17 This suggests that reducing normal physiological levels of glucocorticoid receptor activation can increase the elevation of 5-HT in response to SSRIs.…”
Section: Scientific Backgroundmentioning
confidence: 99%